Impact of co-culturing with fractionated carbon-ion-irradiated cancer cells on bystander normal cells and their progeny - Autsavapromporn N. (2017)
© 2017 by Radiation Research Society. The purpose of this study was to compare the biological effects of fractionated doses versus a single dose of high-LET carbon ions in bystander normal cells, and determine the effect on their progeny using the layered tissue co-culture system. Briefly, confluent human glioblastoma (T98G) cells received a single dose of 6 Gy or three daily doses of 2 Gy carbon ions, which were then seeded on top of an insert with bystander normal skin fibroblasts (NB1RGB) growing underneath. Cells were co-cultured for 6 h or allowed to grow for 20 population doublings, then harvested and assayed for different end points. A single dose of carbon ions resulted in less damage in bystander normal NB1RGB cells than the fractionated doses. In contrast, the progeny of bystander NB1RGB cells co-cultured with T98G cells exposed to fractionated doses showed less damage than progeny from bystander cells co-cultured with single dose glioblastoma cells. Furthermore, inhibition of gap junction communication demonstrated its involvement in the stressful effects in bystander cells and their progeny. These results indicate that dose fractionation reduced the late effect of carbon-ion exposure in the progeny of bystander cells compared to the effect in the initial bystander cells.